Improvement of peat soil chemistry using different types of legume cover crop / Izzatul Akmal Azmi - Azmi, Izzatul Akmal (Faculty of Plantation and Agrotechnology, 2018)
Oil palm plantation usually planted in the deep, well drained and fertile fine soil to clay loams and less planted on peat soil due to it poor physical and chemical characteristics. Hence, it is important to improve the physical as well as chemical properties of peat soils to ensure the oil palm planted is thrive well in such soils. This study aims to identify and to assess the improvement of peat soil chemistry using different types of leguminous cover crops (LCC). In this study, soil samples were obtained from Parit Yusof, Muar, Johore using a random sampling technique. The samples were filled in polybags and treated with four (4) different types of LCC namely Pueraria javanica (T1), Centroma pubescens (T2), Mucuna bracteata (T3) and Colopoganium mucuinodes (T4). Based on the findings, it is showed that Mucuna bracteata was able to improve the soil chemical properties compare to other LCCs. This is due to the highest content of nutrient and better soil pH compared to other types of LCCs.